Mapping sustainable practices in ship recycling - da Silveira, Camila Aparecida Maciel [UNESP] (2025)
This study highlights the importance of the ship recycling industry, especially in developing countries. It notes the growing number of ships being dismantled as they end their operational lives. The study aims to address the efficient end-of-life management of ships, a need that is implicitly highlighted throughout the research. The explicit objective stated is to map the best practices for the ship dismantling process, which involves examining and analyzing factors generated by this process. The methodology described is qualitative and exploratory, based primarily on a literature review. This approach suggests that the study synthesizes existing knowledge and identifies themes related to ship dismantling. The results are categorized into management, environmental, and occupational health and safety. In the management category, the principal issue was the lack of communication between stakeholders, and the recommendation was to create a schedule for improving communication. In the environmental category, water pollution had a significant contribution, and the suggestion is to use more sustainable technologies. Finally, employee injuries were identified in the health and safety category, and the recommendation is to provide training and personal protective equipment. This study concludes that implementing more sustainable and safe practices in dismantling and recycling operations represents a significant advancement for the ship recycling industry, which is anticipated to experience substantial growth in the coming years.